Exploring the complexity of smallholders' intense use of glyphosate in maize crops from South Mexico: Remarks for an ongoing agroecological transition - Monroy-Sais, Ana Sofía; Astier, Marta; Wies, Germán; Pavesi, Riccardo; Mascorro-de Loera, Daniel; García-Barrios, Luis (Frontiers in Sustainable Food Systems, 2022)
Recently, Mexico has launched policies of agroecological transition that seek to foster healthier agri-food systems. One of these policies is the reduction and eventual elimination of glyphosate by 2024. Despite being the most used herbicide in Mexico and the world, little information exists about what factors determine a greater or reduced use of glyphosate in different socio-ecological contexts. This study aimed to explore different agricultural management, biophysical and social variables and their effects on glyphosate use in maize crops by smallholders (<8 ha). A questionnaire and semi-structured interviews were performed with 142 farmer families in four regions of the state of Chiapas to document the use of herbicides and glyphosate. By using regression trees, we identified those variables that determine a greater or lesser use of glyphosate for each region and jointly. The average volume of glyphosate for the four regions during an agricultural cycle was 2.7 l/ha−1. Sets of variables were associated with syndromes of greater use of glyphosate and herbicides in general, such as small plots (<0.67 ha), indigenous population, younger farmers, fewer family members, rainfed conditions, and plots without mechanization. These results can help the design of contextualized and flexible policies of transition, consistent with the socio-ecological heterogeneity of Mexico.